Comparison of pattern of death during Pre-lockdown period and COVID 19 lockdown period in Central Kerala – An Autopsy Study - Babu, Shilpa S; Raveendran, Renju; KA, Anwar (Asian Journal of Medical Sciences, 2021)
Background: The coronavirus pandemic is one of the deadliest pandemic in history. The authorities worldwide responded to this pandemic by implementing business closures, travel restrictions, lockdowns and quarantines. Aims and Objectives: To determine the type of cases and compare the patterns of deaths which came for autopsy to Department of Forensic Medicine, Government Medical College, Kottayam during the Pre lockdown period in 2019 and COVID-19 Lockdown Period in 2020. Materials and Methods: This retrospective study was conducted in the Department of Forensic Medicine, Govt. Medical College, Kottayam. The study data was collected from postmortem reports of Department of Forensic Medicine, Govt. Medical College, Kottayam. Pre-lockdown period was taken as from 21 March to 31 May 2019.There were total 424 cases in 2019,whereas in the Lockdown period taken as from 21 March 2020 to 31 May 2020,no: of cases reduced to 270. All these cases were grouped according to cause of death, manner of death and modalities of natural and unnatural deaths. Details of cases were entered utilizing a proforma. Results: There were total 424 cases in the pre-lockdown period in the year 2019, whereas in the lockdown period in 2020, number of cases declined to 270. Among the manner of deaths, accidents accounted for most of the deaths in the year 2019, i.e. 44.6% deaths due to accidents, whereas in the year 2020, deaths due to natural diseases topped the list, 46.3%. These differences in the manner of deaths were found statistically significant. Conclusion: Two months into lockdown, statistically significant differences were noted in patterns of deaths. Further study should be conducted in the near future, when more data will become available. Providing early warning in patterns of mortality within the community could prove to be an invaluable public health asset.